EVALUASI PENGGUNAAN OBAT PROTON PUMP INHIBITOR PADA PASIEN RAWAT JALAN DENGAN GANGGUAN LAMBUNG (GASTRITIS) DI RUMAH - Maya Syari, Dina; Hotna Sari (JIFI (Jurnal Ilmiah Farmasi Imelda), 2021)
Gastritis is an inflammatory process in the gastric mucosa and gastric mucosa. Gastritis is a state of inflammation or bleeding off the gastric mucosa that is acute, chronic, diffuse, or local. Gastritis or heartburn is an inflammation of the stomach wall, this disease is often found to arise suddenly which is usually characterized by nausea or vomiting, bleeding pain, weakness, decreased appetite or headache. The purpose of this study was to determine the PPI class of drugs most widely used by outpatients with gastric gastritis disorders. Knowing the factors that most often influence of gastric gastritis disorders.To find out the age most often affected by gastric gastritis. This research method used an observational method with the research design used was data collection carried out retrospectively, namely by tracing records at the outpatient installation of Imelda Hospital Medan from January 1 to December 31, 2019. The data obtained at the installation is descriptive and evaluate the use of PPIs with the treatment of gastritis aimed at improving the patient's quality of life, relieving complaints, curing gastritis, preventing recurrences and complications. Besed on the results of the study, the most outpatients with gastritis at the Imleda Hospital Medan were 15 women (17%), 6 men (29%), And the most commonlyused PPI drugs for gastritis patients were lansoprazole in 18 patients (86%), Omeprazole 3 patients (14%).